2018
DOI: 10.1183/16000617.0103-2017
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbations of COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is the third leading cause of death worldwide. While COPD is a mainly chronic disease, a substantial number of patients suffer from exacerbations. Severe exacerbations are related to a significantly worse survival outcome. This review summarises the current knowledge on the different aspects of COPD exacerbations. The impact of risk factors and triggers such as smoking, severe airflow limitation, bronchiectasis, bacterial and viral infections and comorbidities is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
180
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 225 publications
(192 citation statements)
references
References 91 publications
(83 reference statements)
4
180
1
7
Order By: Relevance
“…Over the past decade, the relation between air pollution exposure and AECOPD has been investigated in several studies, but the results were non‐conclusive. Some epidemiological studies have demonstrated that short‐time exposure to air pollution significantly increased the risk of exacerbations, whereas others found no causality or association with only for selected pollutants …”
Section: Smoking and Air Pollutionmentioning
confidence: 99%
See 4 more Smart Citations
“…Over the past decade, the relation between air pollution exposure and AECOPD has been investigated in several studies, but the results were non‐conclusive. Some epidemiological studies have demonstrated that short‐time exposure to air pollution significantly increased the risk of exacerbations, whereas others found no causality or association with only for selected pollutants …”
Section: Smoking and Air Pollutionmentioning
confidence: 99%
“…The eosinophil count is a marker for eosinophilic airway inflammation and a predictive biomarker for the efficacy of ICS treatment in patients with COPD exacerbations . COPD patients with eosinophilia (≥2%) have an increased risk of AECOPD . The first study to investigate the prevalence of blood eosinophilia (defined as ≥300 cells/L) among inpatients with AECOPD evidenced a higher frequency of exacerbations during the 1‐year follow‐up period compared to patients without eosinophilia .…”
Section: Biomarkersmentioning
confidence: 99%
See 3 more Smart Citations